Costs of accessing HIV testing services among rural Malawi communities. (25th July 2018) - Sande, Linda; Maheswaran, Hendramoorthy; Mangenah, Collin; Mwenge, Lawrence; Indravudh, Pitchaya; Mkandawire, Phillip; Ahmed, Nurilign; d'Elbee, Marc; Johnson, Cheryl; Hatzold, Karin; Corbett, Elizabeth L.; Neuman, Melissa; et al.
ABSTRACT: HIV testing is free in Malawi, but users may still incur costs that can deter or delay them accessing these services. We sought to identify and quantify these costs among HIV testing service clients in Malawi. We asked residents of communities participating in a cluster randomised trial investigating the impact of HIV self-testing about their past HIV testing experiences and the direct non-medical and indirect costs incurred to access HIV testing. We recruited 749 participants whose most recent HIV test was within the past 12 months. The mean total cost to access testing was US$2.45 (95%CI: US$2.11–US$2.70). Men incurred higher costs (US$3.81; 95%CI: US$2.91–US$4.50) than women (US$1.83; 95%CI: US$1.61–US$2.00). Results from a two-part multivariable regression analysis suggest that age, testing location, time taken to test, visiting a facility specifically for an HIV test and district of residence significantly affected the odds of incurring costs to testing. In addition, gender, wealth, age, education and district of residence were associated with significant user costs.